Comprehensive analysis of endoplasmic reticulum stress-associated genes signature of ulcerative colitis - Deng, Beiying; Liao, Fei; Liu, Yinghui; He, Pengzhan; Wei, Shuchun; Liu, Chuan; Dong, Weiguo (Frontiers in Immunology, 2023)
Background: Endoplasmic reticulum stress (ERS) plays a crucial role in the pathogenesis of ulcerative colitis (UC), but little is known about its specific molecular mechanisms. This study aims to identify pivotal ERS-related molecular mechanisms in UC pathogenesis and provide novel molecular targets for the treatment of UC. Methods: We obtained the colon tissue gene expression profiles and clinical information of UC patients and healthy control from the GEO database and downloaded the ERS-related gene set from GeneCards for analysis. Weighted gene co-expression network analysis (WGCNA) and differential expression analysis was used to identify the pivotal modules and genes associated with UC. UC patients were classified using a consensus clustering algorithm. CIBERSORT algorithm was adopted to evaluate the immune cell infiltration. Gene Set Variation Analysis (GSVA), Gene Ontology (GO), and Kyoto Encyclopedia of Genes and Genomes (KEGG) were used to explore potential biological mechanisms. Small molecule compounds were predicted using the Connectivity Map (CMap) database. Molecular docking was performed to simulate the binding conformation of small molecule compounds and key targets. We conducted validation in the validation set and explored its relationship with commonly used UC therapeutics. Results: A total of 915 differentially expressed genes (DEGs) and 11 ERS-related genes (ERSRGs) were obtained from the colonic mucosa of UC patients and healthy controls, and the genes had good diagnostic value and correlation with each other. The five potential small-molecule drugs that shared Tubulin inhibitors were screened, including albendazole, fenbendazole, flubendazole, griseofulvin, and noscapine, among which noscapine has the best correlation. Noscapine has a high binding affinity with the target. Active UC and 10 ERSRGs were associated with a large number of immune cells, and ERS was also associated with colon mucosal invasion of active UC. There were significant differences in gene expression patterns and immune cell infiltration abundance among ERS-related subtypes. Conclusion: Our findings suggest that ERS plays a crucial role in UC. Noscapine is expected to be one of the therapeutic agents for UC by affecting ERS.